Perda de pressão estática em uma coluna de grãos de quinoa (Chenopodium quinoa Willd) e análise por elementos finitos - (:unkn) unknown (Universidade Estadual de Goiás, 2012)
Quinoa (Chenopodium quinoa Willdenow) has been indicated as a promising food source. Aspects related to drying and storage of quinoa grains, such as the resistance imposed by the grains to air flow, which is essential in dimensioning of efficient aeration and drying systems, have not been greatly researched. The purpose of this study was to evaluate the effects of air flow on the drop in static pressure in granular masses of quinoa, Real cultivar, with different levels of impurity, adjust the mathematical models to the experimental data obtained, selecting those that best represent the phenomenon, as well as determine the distributed resistance in a granular mass of quinoa with different levels of impurity using the finite element technique. Quinoa, Real cultivar, imported from Bolivia, was purchased in the local market of Goiania, GO. The product was initially free of impurities and with moisture content of 17% d.b. To check the influence of impurities on resistance to air flow, additions of these impurities were made at the percentages of 1, 2, 3, 4, and 5%. Using a piece of equipment duly designed and built and air flows ranging from 0.1 to 0.4 m3 s-1 m-2, the static pressures of clean quinoa and quinoa with impurities were determined. The equations commonly used to describe the phenomenon were adjusted to the experimental data of pressure drop. In addition, modeling was also made using the finite element technique to determine the distributed resistance of the mass of quinoa. The results allow one to conclude that: a) static pressure in a column with quinoa grains increases with the increase in air flow; b) increase in the level of impurity led to reduction in the static pressure drop, with the latter being more affected by the increase in air flow than by the increase in the level of impurities; c) the equations that best represent the experimental data of pressure drop in the inside of the bed with quinoa grains, with and without impurities, were the Shedd and Guimarães equations respectively; d) the distributed resistance in a column with quinoa with different levels of impurity and air flows ranged from 1.24x109 to 4.77x108 m-2; and e) the distributed resistance in a column with quinoa reduced with the increase of air flow and with the increase in the level of impurity.
Keywords: Fluxo de ar; Pressão estática; Resistência ao fluxo de ar; Air flow; Impurities; Resistance to air flow; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA; ENGENHARIA DE PROCESSAMENTO DE PRODUTOS AGRICOLAS::ARMAZENAMENTO DE PRODUTOS AGRICOLAS